2022
DOI: 10.1002/qre.3255
|View full text |Cite
|
Sign up to set email alerts
|

A reliability analysis for electronic devices under an extension of exponentiated perks distribution

Abstract: This paper presents a reliability analysis for electronic devices (ED) with bathtub curve-shaped failure times. An extension of the exponentiated perks distribution (EPD) is proposed for the analysis. The extension of this new distribution is based on the Alpha Power Transformation, so the Alpha Exponentiated Perks Distribution (AEXP) is introduced. The AEXP has three shape parameters and one scale parameter, allowing greater flexibility to represent failure rates in an increasing, decreasing, or bathtub curve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As shown in Figure 9, the failure probability of the FCS increases rapidly at the beginning of usage and then stabilizes, which is consistent with the bathtub curve theory of component reliability 51 . This theory suggests that the failure rate of components typically with a higher initial failure rate during the infant mortality period and a lower rate during the wear‐out period.…”
Section: Case Studysupporting
confidence: 79%
See 1 more Smart Citation
“…As shown in Figure 9, the failure probability of the FCS increases rapidly at the beginning of usage and then stabilizes, which is consistent with the bathtub curve theory of component reliability 51 . This theory suggests that the failure rate of components typically with a higher initial failure rate during the infant mortality period and a lower rate during the wear‐out period.…”
Section: Case Studysupporting
confidence: 79%
“…As shown in Figure 9, the failure probability of the FCS increases rapidly at the beginning of usage and then stabilizes, which is consistent with the bathtub curve theory of component reliability. 51 This theory suggests that the failure rate of components typically with a higher initial failure rate during the infant mortality period and a lower rate during the wear-out period. In the case of aircraft-related components, the failure probability is particularly high during the initial running-in period, due to factors such as manufacturing defects and environmental stresses.…”
mentioning
confidence: 99%
“…The second illustration data set is taken from Mendez-Gonzalez et al 28 . These data, which are shown in Table 13, represent the FTs of 30 DAS cards.…”
Section: Failure Times Of 30 Data Acquisition Systems (Das)mentioning
confidence: 99%
“…Buffinton et al [18] used the Kirton Adaption-Innovation Inventory (KAI) to determine cognitive styles. They concluded that cognitive style theory may be applied to characterize and better understand the personal While engineering design has been explored from various different perspectives, including optimization [2][3][4], reliability [5][6][7][8], manufacturability [9] and decision making [10], among others, there are limited studies of the human dynamics that are inherent to engineering organizations. To gain a better understanding of engineering project management, we clearly need to model the processes and people involved in executing them.…”
Section: Background and Literature Surveymentioning
confidence: 99%